Análise da competição dos bancos privados nas operações de crédito do Sistema Financeiro Nacional - Lourenço, Francis Carlo Petterini (2003)
Since the beginning of the stabilization process of the Brazilian economy in 1994, there has been a strong movement towards the reduction in the number of banks operating in the national financial system. As a consequence of this movement, credit and other bank operations have been concentrated by just a few large banking institutions. In this context, it is necessary to study the competition and the structure of the banking market in Brazil. Based on a sample of the twelve largest private banks in operation since the beginning of the stabilization process and utilizing semi-annual data from their balance sheets, divulged by the Central Bank of Brazil, it was verified that the cartelization hypothesis is strongly rejected. But, the prevailing market structure is, however, oligopolistic.